2016
DOI: 10.1177/0019793916668356
|View full text |Cite
|
Sign up to set email alerts
|

Gender Diversity on U.S. Corporate Boards

Abstract: Despite rhetoric supporting the advancement of women on corporate boards, meager evidence supports significant progress over the past decade in the United States. The authors examine archival board data (for more than 3,000 U.S. publicly traded firms) from 2002 to 2011 and find that a female is most likely to be appointed to a corporate board when a woman has just exited the position. A similar propensity occurs to reappoint a male when a man leaves, although the effect is smaller than for women. The authors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 69 publications
0
26
0
Order By: Relevance
“…Because this alternative measure was highly skewed (less than 8% of the observations had more than one woman on the nominating committee), we decided to use the dummy variable in the analysis. Because firms may add new female directors to fill board vacancies or in anticipation of board vacancies caused by director turnover (Tinsley, Wade, Main, & O'Reilly, ), we used several variables to control for this alternative explanation, including male director turnover (measured by the number of male directors who left the board during the year), female director turnover (measured by the number of female directors who left the board during the year), and incumbent directors' average age and board tenure . We also included board size , measured by the number of directors, to control for the possibility that firms with a larger board may be under stronger external pressure to increase female directors.…”
Section: Methodsmentioning
confidence: 99%
“…Because this alternative measure was highly skewed (less than 8% of the observations had more than one woman on the nominating committee), we decided to use the dummy variable in the analysis. Because firms may add new female directors to fill board vacancies or in anticipation of board vacancies caused by director turnover (Tinsley, Wade, Main, & O'Reilly, ), we used several variables to control for this alternative explanation, including male director turnover (measured by the number of male directors who left the board during the year), female director turnover (measured by the number of female directors who left the board during the year), and incumbent directors' average age and board tenure . We also included board size , measured by the number of directors, to control for the possibility that firms with a larger board may be under stronger external pressure to increase female directors.…”
Section: Methodsmentioning
confidence: 99%
“…In the early 2010s, only 14 percent of directorships were on average held by female directors in the largest European listed companies (European Commission )—a figure comparable with what was observed in the United States (Tinsley et al. ). This disequilibrium in top positions partly reflected the persistence of stereotypes regarding female attributes, values, preferences, and behavior in leadership positions (Gregory et al.…”
Section: Institutional Setting and Research Questionmentioning
confidence: 63%
“…More generally, our finding complements the papers that looked at the effectiveness of institutional pressures to reduce gender inequality in the top executive ranks. These papers showed that diversity innovations had limited effectiveness either because corporations unknowingly used ineffective practices (Dobbin & Kalev, ) or intentionally adopted “symbolic” innovations with very limited effects (Dezső et al, ; Farrell & Hersch, ; Tinsley et al, ). In accordance with these studies, we also show that actions to demonstrate gender diversity in the top executive ranks are often symbolic because they stop after a woman gains access to these top positions; they are only effective for those promoted internally, and they are often granted to women who are of higher ability than their male counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Related research argues that employers view having women in leadership roles as appropriate up to a given proportion but unnecessary or even detrimental above that point. It shows that there are implicit quotas for women in leadership roles that influence women's likelihood of being appointed to managerial jobs (Cohen, Broschak, & Haveman, 1998), top management teams (TMTs; Dezső et al, 2016), and the board of directors (Farrell & Hersch, 2005;Tinsley, Wade, Main, & O'Reilly, 2017).…”
Section: Women's Speed Of Advancement and The Demography Of The Exementioning
confidence: 99%